ASIC for calorimetric measurements in the astrophysical experiment NUCLEON. Issue 4 (January 2016) - Atkin, E; Voronin, A; Karmanov, D; Kudryashov, I; Kovalev, I; Shumikhin, V
Abstract: A satellite with the NUCLEON apparatus was launched in Dec. 2014. The space NUCLEON project of ROSCOSMOS is designed to investigate cosmic ray nuclei energy spectra from 100 GeV to 1000 TeV as well as cosmic ray electron spectra from 20 GeV to 3 TeV. The method of energy determination by means of a silicon instrument for measuring the particle charge of cosmic rays and the calorimetric system were developed. The main parameters, that determine the quality of calorimetric systems are linearity of transfer characteristic and the dynamic range of input signals, which should reach 30 000 MIPs (minimum ionizing particles). The ASIC, satisfying these requirements, consisting of 32 channels with a unique dynamic range from 1 to 40000 MIPs, signal to noise ratio not less than 2.5 at a shaper peaking time of 2 μs and a low power consumption of 1.5 mW/channel has been designed. The first results of the ASIC functionality in space are presented.